Management economics and strategic decision making in the digital age - Mahfud Mahfud; Wawat Hermawati (Goodwood Publishing, 2025)
Purpose: Digital technology reshapes economics and management by enabling faster, data-driven strategic decisions. Companies must adapt to complex market dynamics with innovative, efficient systems. The integration of economics, management, and strategic decision-making strengthens organizational resilience, competitiveness, and sustainability in navigating the challenges of the modern digital era. Research Methodology: Through a managerial economics theoretical approach and case studies of digital companies, this study demonstrates that data- and technology-driven decision-making can improve operational efficiency, innovation, and company competitiveness. Results: This research shows that digital technology significantly influences managerial economics and strategic decisions. Data has become a key strategic asset guiding organizational direction. Companies that utilize big data analytics, artificial intelligence, and ERP systems gain stronger competitive advantages and make faster, more accurate decisions in the digital era. Conclusions: In the digital era, economic management relies heavily on technology and data for strategic decisions. Speed, accuracy, and adaptability determine success. Organizations that integrate digital innovation become more competitive, efficient, and responsive to market change. Thus, digital literacy and transformational leadership are essential in modern management. Limitations: This study has limitations, including a narrow focus on digitalized companies, which may not represent all MSMEs. The descriptive use of secondary data cannot fully explain causal relationships. Rapid technological change also challenges the study’s relevance, as evolving trends may quickly reduce the accuracy of its findings. Contribution: This research offers guidance for managers in integrating information technology to enhance decision effectiveness and competitiveness. It also provides a foundation for future studies exploring how digital transformation influences decision-making across different industrial sectors.